Changing trends in incidence, type, indication and maternal outcome of peripartum hysterectomy over 10 years at a tertiary care centre - Gupta, Taru; Gupta, Sangeeta; Deepika, .; Gupta, Nupur (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Peripartum hysterectomy is the most dramatic operation in modern obstetrics and is generally performed when all conservative measures fail to achieve haemostasis in the setting of life threatening haemorrhage. The objective was to review all peripartum hysterectomies performed at a tertiary care centre over a ten-year period from 2007 to 2016 to determine the incidence, types, indications and maternal outcome and also to study the changing trends Methods: This was a retrospective, observational, analytical study of parturient women requiring peripartum hysterectomy (PH). We looked at data over a ten-year period, from January 2007 to December 2016. Case records were reviewed for socio-demographic characteristics of the patients, type and indications for the hysterectomy performed, booking status of patients, mode of delivery, gestational age at delivery and maternal outcome. Change in trends of the rate and indications of peripartum hysterectomy at the centre was also reviewed. Results: The overall rate of peripartum hysterectomy was 1/876 deliveries. The rate of peripartum hysterectomy had a 4-fold rise from 2007 to 2016.The primary indication was abnormal placentation which included morbidly adherent placentation 22/59 (37.2%) and placentapraevia 5/59 (8.4%), followed by intractable atonic haemorrhage in 35.6% of cases. Abnormal placentation as an indication for PH increased significantly form 34.6% (2007-2011) to 54.54% (2012-2016). After hysterectomy, 56% cases were admitted to ICU. All patients needed blood transfusion. Maternal mortality was 10.1%. Conclusions: Peripartum hysterectomy is a most demanding obstetric surgery performed in very trying circumstances of life threatening hemorrhage. The indication for emergency peripartum hysterectomy in recent years has changed from traditional uterine atony to abnormal placentation.